2019
DOI: 10.1177/0892705719833119
|View full text |Cite
|
Sign up to set email alerts
|

Derived from poplar leaves graphene-modified silicone rubber composites

Abstract: Poplar leaves graphene (PLG) was synthesized from the poplar leaves. Modified poplar leaves graphene (M-PLG) was obtained by graphene treated with silane coupling agent γ-aminopropyltriethoxysilane (KH550). The M-PLG-modified silicone rubber (methyl ethylene silicon rubber [MVQ]) composites were prepared by mechanical blending. The effects of M-PLG on the mechanical properties, thermal properties, and morphology structure of MVQ were investigated. The results showed that the carbon content and purity of the PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Although graphene samples and CGr have the same peak position at 2θ = 26:5°, the peak intensities of the graphene products synthesized at 500-800°C are lower than those of CGr. This result indicates the transformation of graphite to graphene, which is in accordance with literature [33][34][35].…”
Section: Resultssupporting
confidence: 92%
“…Although graphene samples and CGr have the same peak position at 2θ = 26:5°, the peak intensities of the graphene products synthesized at 500-800°C are lower than those of CGr. This result indicates the transformation of graphite to graphene, which is in accordance with literature [33][34][35].…”
Section: Resultssupporting
confidence: 92%
“…However, incorporation of reinforcing particles and/or fibres in polymer matrix has shown good potential in restricting the mobility of their molecular chains on the application of load and/or heat with enhancement in mechanical, thermal, thermomechanical properties, etc. 11,12 On that note, various degrees of improvement in tensile strength, flexural strength, modulus, impact strength, thermal, and thermomechanical properties of PP matrix using CNTs have been reported. 2,5,13 However, the endless need for further improvement in the dispersion and adhesion of CNTs with PP matrix to significantly enhance mechanical, thermal, and thermomechanical properties of PP for various advanced engineering applications formed the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…7,15,16 Various studies have presented enhanced properties of polymer nanocomposites containing CNTs or GNs. For instance, the following engineering properties of polymers have been significantly enhanced using such carbon-based nanofillers; thermal responses, 17,18 mechanical properties, 19,20 wear properties, 21,22 dielectric and electrical properties. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…7,15,16 Various studies have presented enhanced properties of polymer nanocomposites containing CNTs or GNs. For instance, the following engineering properties of polymers have been significantly enhanced using such carbon-based nanofillers; thermal responses, 17,18 mechanical properties, 19,20 wear properties, 21,22 dielectric and electrical properties. 23,24 However, studies have also shown that hybridization of CNTs and GNs in a polymer matrix can result to better mechanical and thermal properties compared to their individual nanocomposites.…”
Section: Introductionmentioning
confidence: 99%